Mesenchymal stromal cells from people with osteoporosis are fewer, and defective in both osteogenic and adipogenic capacity - Féaron C. Cassidy; Ciara Shortiss; Kerry Thompson; Ana Soriano Arroquia; Colin G. Murphy; Stephen R. Kearns; William Curtin; Katarzyna Goljanek-Whysall; Timothy O’Brien; Cynthia M. Coleman (Exploration of Musculoskeletal Diseases)
Aim: Osteoporosis (OP) is caused by imbalanced bone remodelling homeostasis. It is highly prevalent, especially in post-menopausal women, resulting in high risk of fracture and morbidity. Mesenchymal stromal cells (MSCs) are osteoblast progenitors, and orchestrate the function of surrounding cells including osteoblasts. Understanding MSC phenotype and function is therefore critical in discerning the aetiology of OP and developing superior therapies. Currently, adequate long-term therapeutic strategies are not available. Methods: Bioinformatic analysis of ribonucleic acid sequencing (RNA-seq) data revealed differential expression of genes primarily related to osteogenic differentiation and proliferation, followed by confirmatory in vitro analysis. Results: This study identified novel and previously proposed targets for therapeutic intervention in OP. Functional assessment demonstrated reduced MSC number and osteogenic capacity associated with OP. Proliferation was not affected but OP was unexpectedly associated with a reduction in MSC adipogenic differentiation capacity, correlating with donor age. Conclusions: These data indicate specific targets for further studies of future treatments for OP, including the assessment of modified MSCs as therapeutics. Advances in this area may contribute to reducing fracture-associated morbidity and mortality, and improving quality of life for the 200 million people living with OP globally.